The impact of multicast layering on network fairness. - Rubenstein, Dan (Computer communication review.)
Many definitions of fairness for multicast networks assume that sessions are single-rate, requiring that each multicast session transmits data to all of its receivers at the same rate. These definitions do not account for multi-rate approaches, such as layering, that permit receiving rates within a session to be chosen independently. We identify four desirable fairness properties for multicast networks, derived from properties that hold within the max-min fair allocations of unicast networks. We extend the definition of multicast max-min fairness to networks that contain multi-rate sessions, and show that all four fairness properties hold in a multi-rate max-min fair allocation, but need not hold in a single-rate max-min fair allocation. We then show that multi-rate max-min fair rate allocations can be achieved via intra-session coordinated joins and leaves of multicast groups. However, in the absence of coordination, the resulting max-min fair rate allocation uses link bandwidth inefficiently, and does not exhibit some of the desirable fairness properties. We evaluate this inefficiency for several layered multi-rate congestion control schemes, and find that, in a protocol where the sender coordinates joins, this inefficiency has minimal impact on desirable fairness properties. Our results indicate that sender-coordinated layered protocols show promise for achieving desirable fairness properties for allocations in large-scale multicast networks.